Van der Waals heterostructures based on graphene and 2D ferroelectric CuInP2S6 - Dey, Anubhab (2023)
Two-dimensional van der Waals (vdW) ferroelectrics are of great technological interest for high-density electronics, such as non-volatile memories and field-effect transistors, due to their intrinsic ferroelectric polarisation. Their integration with graphene offers opportunities to create ferroelectric/graphene hybrid systems for novel applications, such as ferroelectric field effect transistors. Also in these systems, graphene can provide a sensitive probe of the ferroelectric polarisation, which is difficult to measure in thin ferroelectrics. Within the family of vdW ferroelectrics, CuInP2S6 (CIPS) has attracted widespread attention due to its relatively high Curie temperature (Tc = 315 K), out-of-plane ferroelectricity, ionic conductivity and large optical band gap at room temperature (Eg = 2.7 eV). This thesis focuses on the electrical and optical properties of CIPS in bulk and thin layers. In particular, it explores CIPS/graphene heterostructures and the unique phenomena that emerge from the charge transfer at the CIPS/graphene interface.